1993
DOI: 10.1056/nejm199305273282103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atovaquone (566C80) with Trimethoprim-Sulfamethoxazole to Treat Pneumocystis carinii Pneumonia in Patients with AIDS

Abstract: For the treatment of P. carinii pneumonia, atovaquone is less effective than trimethoprim-sulfamethoxazole, but it has fewer treatment-limiting adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
0
5

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(147 citation statements)
references
References 11 publications
6
132
0
5
Order By: Relevance
“…14,[16][17][18] Hematologic toxicity was uncommon. 17 Atovaquone tablets, used in earlier studies, have been discontinued due to poor bioavailability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[16][17][18] Hematologic toxicity was uncommon. 17 Atovaquone tablets, used in earlier studies, have been discontinued due to poor bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmacokinetic studies have shown a direct correlation between efficacy and the steady-state plasma concentration, 16 steady-state plasma atovaquone concentrations were not studied in the study population. However, in a small series of solid organ transplant patients at this center adequate atovaquone serum levels (levels exceeding the MIC for P. carinii) were achieved after a prophylactic dosing regimen of 1500 mg daily of atovaquone.…”
Section: Discussionmentioning
confidence: 99%
“…The stomach, small bowel, and colon are frequently the sites of involvement, even in the absence of detectable disease (22). In addition, hypochlorhydria has been well documented in patients with AIDS (23 (20). In addition, incomplete healthy volunteers (12,15,16,19,26 …”
Section: Methodsmentioning
confidence: 99%
“…Maximum plasma concentrations exceeded 30000 ng/mL in HIV-infected men dosed with 750 mg ATQ twice daily (16). Further, plasma ATQ concentrations of 10000 -15000 and 15000 -20 000 ng/mL have been associated with 79% and 95% treatment success in patients infected with HIV and presenting with Pneumocystis pneumonia (17). ATQ drug concentrations may be lower if used prophylactically for prevention (10).…”
Section: Discussionmentioning
confidence: 99%